2017
DOI: 10.1002/prot.25314
|View full text |Cite
|
Sign up to set email alerts
|

Role of N‐glycosylation in EGFR ectodomain ligand binding

Abstract: The epidermal growth factor receptor (EGFR) is a tyrosine kinase protein, overexpressed in several cancers. The extracellular domain of EGFR is known to be heavily glycosylated. Growth factor (mostly epidermal growth factor or EGF) binding activates EGFR. This occurs by inducing the transition from the autoinhibited tethered conformation to an extended conformation of the monomeric form of EGFR and by stabilizing the flexible preformed dimer. Activated EGFR adopts a back-to-back dimeric conformation after bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 61 publications
(132 reference statements)
0
26
0
Order By: Relevance
“…EGFR has a complex mechanism of regulation involving receptor oligomerization, lipid raft localization, shedding, and dynamic partitioning between cellular compartments including the plasma membrane, endosome and nucleus [ 42 45 ]. Many of these processes are known to be influenced by EGFR glycan composition [ 39 , 46 48 ]. Furthermore, glycosylation modulates the overall conformation of EGFR in the absence of ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR has a complex mechanism of regulation involving receptor oligomerization, lipid raft localization, shedding, and dynamic partitioning between cellular compartments including the plasma membrane, endosome and nucleus [ 42 45 ]. Many of these processes are known to be influenced by EGFR glycan composition [ 39 , 46 48 ]. Furthermore, glycosylation modulates the overall conformation of EGFR in the absence of ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular domain of EGFR is heavily N -glycosylated and the glycosylation pattern is implicated in receptor dimerization and subsequent activation 53,54 . Interestingly, the crystal structure of Chi3l3 revealed a saccharide-binding site 55 and functional studies showed that Chi3l3 exhibited binding specificity to saccharides with free amine groups, including glucosamine (GlcN) and GlcN-polymers 56 , making it compatible with binding to EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity of EGFR activation is mediated through the establishment of defined contacts between the ligand and the binding groove of the receptor located on its extracellular face (Bajaj et al, 1987;Lax et al, 1988;Ferguson et al, 2003;Jorissen et al, 2003;Zhu et al, 2017). Variations in sidechain features between different ligands, as well as posttranslational modifications present on the extracellular EGFR domain, determine the strength of engagement (Azimzadeh Irani et al, 2017). Solid-state nuclear magnetic resonance (NMR) experiments have demonstrated that, in the absence of ligand, the intracellular region of EGFR exists in a rigid conformation, while the extracellular domain remains highly dynamic.…”
Section: Introductionmentioning
confidence: 99%